2019
DOI: 10.3390/cells8060519
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as an Inflammatory Agent Can Cause Cellular Changes in Human Milk due to the Actions of the Adipokines Leptin and Adiponectin

Abstract: Adiponectin and leptin play roles in the hunger response, and they can induce the inflammatory process as the initial mechanism of the innate immune response. It is possible for alterations in the levels of these adipokines to compromise the functional activity of human colostrum phagocytes. Therefore, the objective of this study is to analyze the effects of adiponectin and leptin on colostrum mononuclear (MN) cells. Colostrum was collected from 80 healthy donors, who were divided into two groups: the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 55 publications
1
15
0
7
Order By: Relevance
“…This is consistent with the finding that leptin can reduce oxidative stress and decrease apoptosis in other cells (Balasubramaniyan et al, 2007;Kaeidi et al, 2019). Morais et al (2019) have shown that leptin can activate the classical nuclear factor-κB pathway, which can regulate the genes responsible for ROS production.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the finding that leptin can reduce oxidative stress and decrease apoptosis in other cells (Balasubramaniyan et al, 2007;Kaeidi et al, 2019). Morais et al (2019) have shown that leptin can activate the classical nuclear factor-κB pathway, which can regulate the genes responsible for ROS production.…”
Section: Discussionsupporting
confidence: 91%
“…Obesity and diabetes are related to a higher incidence and severity of infectious diseases and involve different cells and immune mechanisms [ 41 ]. In addition, the immunological factors observed cause alterations in the percentage and function of cell, cytokine, antibody, and adipokine levels [ 18 , 42 , 43 ], suggesting changes in inflammatory mediators [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition and some nutrients can influence the immune system and regulate directly by signaling pathways, as well as regulating hormones that, in turn, modulate the immune system. [30]. In this study, melatonin adsorbed to PEG microspheres exhibited anti-tumor activity against MCF-7 human breast cancer cells, especially when in coculture with colostrum MN cells, and this activity oscillated as a function of the time of day.…”
Section: Discussionmentioning
confidence: 60%